Update on the pathogenesis of osteolysis in multiple myeloma patients - Giuliani, N.; Colla, S.; Rizzoli, V. (Acta Biomedica Atenei Parmensis, 2004)
Multiple myeloma (MM) is a plasma cell malignancy characterized by the high capacity to induce osteolytic bone lesions that mainly result from an increased bone resorption related to the stimulation of osteoclast recruitment and activity. Although it is known that myeloma cells induce osteoclastic bone resorption, the biological mechanisms involved in the pathophysiology of MM-induced bone resorption have been unclear for several years. Recently, new data seem to elucidate which mechanism is critically involved in the activation of osteoclastic cells in MM. The critical osteoclastogenetic factor RANKL and its soluble antagonist osteoprotegerin (OPG) are the major candidates in the pathophysiology of MM bone disease. Human MM cells induce an imbalance in the RANKL/OPG ratio in the bone marrow environment that triggers the osteoclast formation and activation leading to bone destruction. The role or RANKL/OPG system and other osteoclast stimulating factors in the pathophysiology of MM bone disease are summarized in this update.